2020
DOI: 10.1089/jmf.2019.0030
|View full text |Cite
|
Sign up to set email alerts
|

Sepiolite Clay Attenuates the Development of Hypercholesterolemia and Obesity in Mice Fed a High-Fat High-Cholesterol Diet

Abstract: Obesity reduces the quality of life and life expectancy, whereas nonoperative interventions have shown poor results so far. Statins effectively combat hypercholesterolemia but are not well tolerated at high doses, raising the need for coprescription with cholesterol sorbents and/or absorption inhibitors. Montmorillonite (MMT) clay was found to attenuate hypercholesterolemia and obesity by reducing cholesterol and fat absorption. However, acicular clay-like sepiolite may offer better results due to its more sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The ability for LAP, MMT, and MPS to adsorb organic species, specifically lipid and carbohydrate species, was assessed at the completion of in vitro GI lipolysis since it is hypothesized that lipid and carbohydrates adsorbed within the porous matrices of particulate materials are no longer available for absorption across the intestinal epithelium and are therefore excreted from the body. , MMT revealed the greatest capacity to adsorb organic species under digesting conditions simulating the fed state, adsorbing 156 ± 43 mg of organics, which correlates with over 10% of the organic media available for adsorption within the lipolysis media (Figure A). Lipid speciation studies, using 1 H NMR, revealed that MMT indiscriminately adsorbs fatty acids and glycerides (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability for LAP, MMT, and MPS to adsorb organic species, specifically lipid and carbohydrate species, was assessed at the completion of in vitro GI lipolysis since it is hypothesized that lipid and carbohydrates adsorbed within the porous matrices of particulate materials are no longer available for absorption across the intestinal epithelium and are therefore excreted from the body. , MMT revealed the greatest capacity to adsorb organic species under digesting conditions simulating the fed state, adsorbing 156 ± 43 mg of organics, which correlates with over 10% of the organic media available for adsorption within the lipolysis media (Figure A). Lipid speciation studies, using 1 H NMR, revealed that MMT indiscriminately adsorbs fatty acids and glycerides (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, increasing attention has been afforded to food-grade biomaterials that exert anti-obesity effects through the impediment of fat digestion and absorption pathways . Of such materials, high surface area colloids, such as smectite clays and mesoporous silica, have demonstrated excellent promise in provoking weight reductions when supplemented to rodents exposed to high-fat diets (HFDs). Since the physiological mechanism of lipid (fat) digestion is modulated by the ability for digestive enzymes, specifically gastric and pancreatic lipases, to access and adsorb at the lipid droplet interface, , colloids can restrict digestion by competitively interfering and “spoiling” the lipid surface. , In doing so, the degree of lipid species available for digestion and absorption across the intestinal epithelium is reduced, leading to an overall reduction in energy intake. Furthermore, porous colloids have high specific surface areas and, therefore, high adsorptive capacities, which can lead to the adsorption of dietary fats within the gastrointestinal (GI) tract, thus promoting lipid excretion .…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of CBZ on sepiolite is negligible (Figure 1A). This is not obvious, since several non-charged molecules and oils are adsorbed in large amounts on this clay [72,73]. As for the smectites, organoclay based on BZK exhibited the lowest adsorption, whereas raw bentonite and Ca-SWy-1 adsorb more than 0.5 mmol g −1 .…”
Section: Adsorption Isothermsmentioning
confidence: 94%
“…Adsorption of CBZ on sepiolite is negligible. This is not obvious, since several noncharged molecules and oils are adsorbed in large amounts on this clay [67,68]. As for the smectites, organoclay based on BZK exhibited the lowest adsorption, whereas raw bentonite and Ca-SWy-1 adsorb more than 0.5 mmol g -1 .…”
Section: Adsorption Isothermsmentioning
confidence: 95%